Investigations of secondary electron emission from boron doped diamond films grown by MPCVD - Ding, M. Q.; Lili Li; Jinjun Feng; Yujuan Gao; Qilue Chen; Wensheng Shao (IVESC 2012, 2012)
A high secondary yield of 18.3 at 1KeV primary beam energy was found, with the B-doped diamond sample left in air for weeks and subject to no treatment prior to the measurement. Oxidation treatment destroys negative electron affinity (NEA) whereas heating in vacuum substantially regains NEA.